The methodology of the Austrian school of economics: The present state of knowledge - Wiśniewski, Jakub Bożydar (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This paper is an attempt to systematize the methodological insights and contributions of the Austrian School of Economics and present them in their most up-to-date elaboration, thereby building on the earlier literature on the subject. It aims to improve on the publications listed above in two aspects. First, it takes into account the most recent conceptual developments that address some of the common misunderstandings of the Austrian methodological position, as well as some of its more insightful contemporary criticisms. Second, it organizes the presentation of the relevant material around several clearly specified methodological dimensions, while, in contrast to most of the abovementioned literature, keeping the description of the historical background behind the development of the Austrian method to an absolute minimum, as well as leaving out the non-methodological differences between the ASE and its intellectual rivals, thus aiming to make the presentation in question maximally focused and thematically unified
Keywords: szkoła austriacka; Menger, Carl (1840-1921); Mises, Ludwig von (1881-1973); aprioryzm; prakseologia; pozytywizm; empiryzm